All in the family: Money, kinship and Theravada monasticism in Nepal - Gellner, David N; LeVine, Sara (Occasional Papers in Sociology and Anthropology, 2008)
DOI: 10.3126/opsa.v10i0.1150 Occasional Papers in Sociology and Anthropology Vol.10 2007 p.141-173